Can targeted messages reduce COVID-19 vaccination hesitancy? A randomized trial - Reddinger, J. Lucas; Levine, David; Charness, Gary (Preventive medicine reports, 2022)
•We find no evidence that tailoring public health communication regarding COVID-19 vaccination for broad demographic groups would increase its effectiveness.•A post hoc analysis finds that a vaccine endorsement from Dr. Fauci reduces stated intent to vaccinate among conservatives.•We recommend further research on communicators and endorsers, as well as incentives. Widespread vaccination is certainly a critical element in successfully fighting the COVID-19 pandemic. We apply theories of social identity to design targeted messaging to reduce vaccine hesitancy among groups with low vaccine uptake, such as African Americans and political conservatives. Participants. We conducted an online experiment from April 7 to 27, 2021, that oversampled Black, Latinx, conservative, and religious U.S. residents. We first solicited the vaccination status of over 10,000 individuals. Of the 4,609 individuals who reported being unvaccinated, 4,190 enrolled in our covariate-adaptive randomized trial. Interventions. We provided participants messages that presented the health risks of COVID-19 to oneself and others; they also received messages about the benefits of a COVID-19 vaccine and an endorsement by a celebrity. Messages were randomly tailored to each participant’s identities—Black, Latinx, conservative, religious, or being a parent. Outcomes. Respondents reported their intent to obtain the vaccine for oneself and, if a parent, for one’s child. We report results for the 2,621 unvaccinated respondents who passed an incentivized manipulation check. We find no support for the hypothesis that customized messages or endorsers reduce vaccine hesitancy among our segments. A post hoc analysis finds evidence that a vaccine endorsement from Dr. Fauci reduces stated intent to vaccinate among conservatives. We find no evidence that tailoring public-health communication regarding COVID-19 vaccination for broad demographic groups would increase its effectiveness. We recommend further research on communicators and endorsers, as well as incentives.